Correlation of SUV-Derived Indices With Tumoral Aggressiveness of Gliomas in Static 18F-FDOPA PET: Use in Clinical Practice. (September 2015) - Janvier, Lucile; Olivier, Pierre; Blonski, Marie; Morel, Olivier; Vignaud, Jean-Michel; Karcher, Gilles; Taillandier, Luc; Verger, Antoine
Abstract : Purpose: Glioma grading is necessary for prognostic evaluation and optimal treatment decisions. The aims of this study were to establish whether a correlation between 18 F-FDOPA uptake with tumor grade was observed and to determine which of the SUV-derived indices was the best correlated. Patients and Methods: Thirty-one patients were retrospectively included (mean [SD] age, 36.8 [12.1] years) including 21 proven low-grade tumors due to histology, imaging, and clinical follow-up and 10 histologically proven high-grade tumors. Static PET acquisitions were postreconstructed between the 10th and 30th minute after injection of 18 F-FDOPA. Regions of interest of 20 mm were applied to tumors, and isocontoured volumes were defined at levels of 50% and 80% of the peak intensity voxel. Background was quantified with 30-mm-diameter regions of interest on contralateral striatum and centrum semioval. Tumoral uptake was evaluated with the following SUV-derived indices: SUVmax, SUVmean, SUVmax, and SUVmean of isocontoured volume, tumor/striatum ratio (T/S), and tumor/normal brain ratio (T/N). Results: All the SUV-derived indices tested were significantly correlated with tumor grade, considering low-grade and high-grade groups ( P < 0.05), except for the SUVmean 50%. The 2 best-correlated indices were SUVmean T/N and SUVmean T/S, with correlation coefficients of 0.561 and 0.522, respectively. Receiver operating characteristic analysis defined optimal thresholds of 1.33 and 1 for sensitivity and specificity of 71% and 100% and 67% and 100%, respectively. Conclusions: 18 F-FDOPA PET SUV-derived indices are routinely available information that enables accurate discrimination of low-grade and high-grade gliomas. The best-correlated indices were SUVmean T/N and SUVmean T/S with thresholds of 1.33 and 1.